Influence of Changes in the Evaluation of Neonatal Jaundice - Riskin, Arieh; Cohen, Keren; Kugelman, Amir; Abend-Weinger, Marta; Hemo, Miri; Bader, David (American Journal of Perinatology, 2014)
Objective To study the influence of policy changes in the evaluation of neonatal hyperbilirubinemia on discharge process from the nursery. Changes included early assessment of risk factors by universal umbilical blood sampling for blood type, Coombs test, and glucose-6-phosphate dehydrogenase (G6PD) and universal noninvasive transcutaneous bilirubinometry at discharge.Study Design The 1,569 newborns (≥ 36 weeks' gestation) admitted after the implementation of changes were compared with the 1,822 born before.Results Policy changes improved the diagnosis of G6PD deficiency and ABO incompatibility and decreased the number of referrals from the community for jaundice follow-up. The average number of needlesticks per baby as well as the time required for the analysis of serum bilirubin levels on discharge day decreased. Changes did not significantly increase costs.Conclusion Changes seem to have improved the quality of medical care, including early identification of risk factors and better follow-up of neonatal hyperbilirubinemia with reduction of pain and increased efficiency.
Keywords: policy changes; evaluation; neonatal jaundice; risk factors; quality measures